Hierarchically porous cobalt-carbon nanosphere-in-microsphere composites with tunable properties for catalytic pollutant degradation and electrochemical energy storage - Liu, Yu; Wang, C.; Veder, Jean-Pierre; Saunders, M.; Tade, Moses; Wang, Shaobin; Shao, Zongping (Academic Press, 2018)
Unreliable energy supply and environmental pollution are two major concerns of the human society in this century. Herein, we report a rational approach on preparation of hierarchically-structured cobalt-carbon composites with tunable properties for a number of applications. A facile hydrothermal treatment of cobalt nitrate and sucrose results in the formation of a metallic cobalt-amorphous carbon composite with cobalt nanospheres anchored homogenously on an amorphous carbon substrate. Tuning the calcination conditions in air will generate either a metallic cobalt-cobalt oxide core-shell structure with magnetism or a fully oxidized Co3O4 composite. The different materials are demonstrated as anodes for lithium-ion batteries (LIBs) and catalysts for advanced oxidation-based wastewater remediation. A fully oxidized composite (FC@CS, fully oxidized Co loaded on carbon spheres) as a LIB anode exhibits superior electrochemical performance, possessing a high reversible capacity, high initial columbic efficiency, outstanding cycling performance and excellent rate capability. The anode performance is superior to most reported Co3O4-based electrodes. Meanwhile, the partially oxidized composite (PC@CS, partially oxidized Co loaded on carbon spheres) functions as an efficient and stable catalyst for removal of phenol via peroxymonosulfate (PMS) activation, which is demonstrated via electron paramagnetic resonance (EPR) and quenching experiments for generation of radicals. More importantly, the recycled PC@CS can be further applied as a LIBs anode after full oxidation regeneration, performing comparably to FC@CS. This FC@CS → PC@CS → FC@CS transformation provides an innovative approach for efficient material synthesis, recycling and application.